2016
DOI: 10.1016/j.watres.2016.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Impact of microbial physiology and microbial community structure on pharmaceutical fate driven by dissolved oxygen concentration in nitrifying bioreactors

Abstract: Operation at low dissolved oxygen (DO) concentrations (<1 mg/L) in wastewater treatment could save utilities significantly by reducing aeration energy costs. However, few studies have evaluated the impact of low DO on pharmaceutical biotransformations during treatment. DO concentration can impact pharmaceutical biotransformation rates during wastewater treatment both directly and indirectly: directly by acting as a limiting substrate that slows the activity of the microorganisms involved in biotransformation; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(35 citation statements)
references
References 69 publications
1
31
0
Order By: Relevance
“…As previously described (Section 3.2), the higher microbial richness observed in the biofilm enriched with methanol could have likely contributed to the overall higher micropollutant biotransformation in the methanol-dosed MBBR. Similarly, positive associations between biodiversity and the rates of specific micropollutant biotransformations were observed in activated sludge (Johnson et al, 2015;Stadler and Love, 2016) and MBBR (Torresi et al, 2016).…”
Section: Influence Of Dosed Carbon Source On Micropollutants Biotransmentioning
confidence: 68%
See 1 more Smart Citation
“…As previously described (Section 3.2), the higher microbial richness observed in the biofilm enriched with methanol could have likely contributed to the overall higher micropollutant biotransformation in the methanol-dosed MBBR. Similarly, positive associations between biodiversity and the rates of specific micropollutant biotransformations were observed in activated sludge (Johnson et al, 2015;Stadler and Love, 2016) and MBBR (Torresi et al, 2016).…”
Section: Influence Of Dosed Carbon Source On Micropollutants Biotransmentioning
confidence: 68%
“…Thus, microbial communities in postdenitrifying systems using either of these carbon sources may be fundamentally different and potentially exhibit a different biodiversity and functionality with more or less microbial specialists able to biotransform organic micropollutants. Additionally, biodiversity in terms of species richness (the number of species) and evenness (the relative abundance of the species) (Wittebolle et al, 2009) was shown to positively associate with the biotransformation of a number of micropollutants in aerobic activated sludge (Johnson et al, 2015;Stadler and Love, 2016) and nitrifying MBBRs (Torresi et al, 2016). Further investigation of the impact of biodiversity in different biological treatment systems seems thus required.…”
Section: Introductionmentioning
confidence: 99%
“…One way to enhance the loss of compounds that undergo these types of biotransformation processes may be to design WWTPs to support diverse microbial communities and harness specific low‐abundance community members. Recent studies suggest that certain WWTP operational parameters, such as solids retention time (Vuono et al ., 2016), dissolved oxygen conditions (Stadler and Love, 2016), and concentration and composition of dissolved organic matter (Li et al ., 2014) can all influence the degree of microbial biodiversity and the extent of micropollutant removal. Further research is needed to understand the relative importance of these operational parameters and environment conditions and others on WWTP microbial biodiversity and pharmaceutical biotransformation.…”
Section: Discussionmentioning
confidence: 99%
“…1, 2 The discovery of comammox bacteria has redefined a key component of the global nitrogen cycle, initiating a renewed focus of recent nitrogen cycling research in environmental biotechnology. 38…”
Section: Introductionmentioning
confidence: 99%